DIVERSIFICATION OF PRODUCTION AS A DIRECTION OF STRATEGIC DEVELOPMENT OF ENTERPRISES (Mongolian Journal of Agricultural Sciences, 2017)
Currently, production diversification strategy is one of the primary tasks of the Republic of Kazakhstan and Mongolia. In particular, the question of the relevance of diversification of production in crop farming, is particularly acute in terms of ensuring the sustainability of agricultural production, restructuring the production in line with market conditions, achieving economic efficiency of crop production. There are a number of issues to be solved for the effective use of the diversification of production in crop production, such as:• the negative impact of risks, reduction of volumes of sales and profitability of crop production (economic);• underutilization of production capacity, not fully used working capital (technology);• cyclical nature of economic development, slow pace of development of scientific and technological progress, the uneven development of sectors of the economy (organizational);• deterioration of soil quality and land used in crop production (ecology).